Escola da Terra Program in Paraná: a reference of university extension in the policy of continuing education of teachers - Ana Cristina Hammel; Marcos Gehrke (Universidade Federal do Norte do Tocantins, 2022)
This text deals with the School to Land Programme, a public policy for the continuing teachers education in rural schools, linked to the National Program of Rural Education, of the Ministry of Education (MEC), presenting the experience developed in the State of Parana since the university extension carried out by public universities. It makes use of bibliographical research and document analysis, from the projects, reports and publication already developed, work mediated by conjuncture analysis. It highlights the need for continuing teachers education, demarcates characteristics and principles of what is an Earth School and reveals significant setbacks in public investments in the program.